Developing the mortgage sector in Nigeria through the provision of long-term finance : an efficiency perspective - Johnson, Paul Femi (Cranfield University, 2014)
This research investigates the role of efficiency in attracting long-term finance to the mortgage sector. Within the framework of the traditional economic theory, the new institutional theory and the theory of mortgage collateral, the study investigates the efficiency of primary mortgage banks and the perceived efficiency of the larger system within which they operate using quantitative and qualitative techniques. Quantitative data were extracted from the financials of 27 mortgage banks in Nigeria, which constitute about 90% of the size of the entire industry in Nigeria, as measured by banks’ total assets. These were analyzed using data envelopment analysis (DEA) and stochastic cost frontier (SCF) analysis to determine the efficiency of mortgage banks in Nigeria. In-depth interviews and focus group discussions were conducted among 40 CEOs of mortgage banks in Nigeria to investigate the perceived efficiency of both the banks and the entire mortgage sector. This sample constitutes about 54.2% of the CEOs in the industry and represents all geopolitical zones and ethnic groups where mortgage banks exist in the country. A review of housing finance policies, systems and sources of funds in thriving emerging economies was also conducted with the aim of drawing lessons from them that are applicable to improving the efficiency of the Nigerian mortgage sector. The findings from the review formed the basis of a mixed method questionnaire survey to investigate the existing and potential sources of funds for housing finance, to assess the acceptability and suitability of lessons drawn from other countries in Nigeria and to make policy recommendations for improving the efficiency of the Nigerian mortgage sector. The findings reveal that on average, mortgage banks in Nigeria are 33% - 49% efficient compared to best practice firms within the sector. Ownership structure and bank size influence the efficiency of these banks. Banks owned by private organizations and commercial banks are more efficient than those owned by the government or religious organizations. Banks with average total assets in excess of ₦5 Billion are more technically efficient than those with total asset less than ₦5 Billion. Practitioners perceive the mortgage banks and the larger system within which they operate as only about 10% efficient. This perceived efficiency is much lower than the technical efficiency measured in the quantitative assessment. Through the lens of institutional theory, this low rating is attributed to the negative perception of the institutional structures of the mortgage sector by mortgage finance practitioners. The findings also reveal that two categories – external and internal factors – impair the efficiency of the sector. The regulative constraints account for 55% of challenges to efficiency, normative constraints account for 24%, while cultural cognitive constraints account for 21%. The study identified accumulated deposits in pension funds, unclaimed dividends, funds in dormant accounts of commercial banks and other financial institutions, and funds from insurance companies, as possible sources of long-term funds for housing finance, while a concerted effort is being made to set up a secondary mortgage facility. The findings also reveal that effective government policies, regulation and amendment of existing laws would help improve the efficiency of the mortgage banking sector and attract investors to this sector.
Keywords: Efficiency; Housing finance; Mortgage sector; Enabling policies; Nigeria